2015
DOI: 10.3892/ol.2015.3025
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor in hepatocarcinogenesis: Recent developments and perspectives

Abstract: Abstract. Previous studies have indicated that males are at a higher risk of developing hepatocellular carcinoma (HCC) compared with females. Identifying the factors that cause this gender-specific difference in the incidence of HCC has long been considered important for revealing the molecular mechanisms involved in hepatocarcinogenesis. Given the unprecedented tools that are now available for molecular research, genetic studies have established that the androgen receptor (AR) may be partly responsible for ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…The significant change in the gene expression profile of AR not only between young normal liver cells and young liver cancer cells ( p -value < 2.46☓10 -6 ) but also between old normal liver cells and old liver cancer cells ( p -value < 6.13☓10 -7 ) implicates that the gene expression change of AR may be required for hepatocarcinogenesis. The result can be supported by the most recent study in hepatocarcinogenesis [ 91 ]. HIV-1 Infection …”
Section: Discussionsupporting
confidence: 70%
“…The significant change in the gene expression profile of AR not only between young normal liver cells and young liver cancer cells ( p -value < 2.46☓10 -6 ) but also between old normal liver cells and old liver cancer cells ( p -value < 6.13☓10 -7 ) implicates that the gene expression change of AR may be required for hepatocarcinogenesis. The result can be supported by the most recent study in hepatocarcinogenesis [ 91 ]. HIV-1 Infection …”
Section: Discussionsupporting
confidence: 70%
“…As there are significantly fewer patients with HBV‐related HCC in C2 compared to C1, one possible explanation for the greater reduction of HCC in the male compared to the female population in C2 is the greater impact of HBV treatment in male patients compared to female patients. It has been shown that due to differential sex hormone and androgen receptor activity, HBV replication is approximately twice as efficient in male mice, which is one reason for the sex discrepancy of HBV‐related HCC 41. We postulate that the advent of highly effective nucleotide/nucleoside analogue therapy for HBV in C2 has resulted in better viremic control of HBV overall and consequently reduced HBV‐related hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies had revealed the estrogen as a protect factor in this accident [29], but the effect of androgen/AR axis seems pleiotropic [30]. In recent years, increasing evidences have considered androgen/AR axis as a motivator for tumorigenesis in prostate, liver and some other organs [31, 32], which enriched our understanding of HCC gender disparity phenomenon, but the exact mechanisms are still largely unrevealed.…”
Section: Discussionmentioning
confidence: 99%